2016
DOI: 10.1111/jep.12624
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with use of falls risk–increasing drugs among patients of a geriatric oncology outpatient clinic in Australia: a cross‐sectional study

Abstract: Older people with cancer are at increased risk of falling. Falls risk-increasing drugs (FRIDs), comprising psychotropics and medications that cause orthostatic hypotension, are a potentially modifiable risk factor for falls. The objective of this study was to determine the prevalence and factors associated with use of FRIDs in older people with cancer. Patients aged ≥70 years who presented to a hospital outpatient clinic between January 2009 and July 2010 were included in the study. Information on current medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…It is accepted that good clinical practice would involve not initiating an FRID in an older adult at high falls risk unless it is absolutely necessary. However, previous research has suggested clinicians may under-recognize the contribution of medications to falls (Bell et al, 2015;Turner et al, 2017). Whether clinicians consider residents' falls risk when initiating FRIDs has important implications because medications are a modifiable risk factor for falling, and avoidance of FRIDs may be an important strategy to minimize the risk of falls and fall-related injuries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is accepted that good clinical practice would involve not initiating an FRID in an older adult at high falls risk unless it is absolutely necessary. However, previous research has suggested clinicians may under-recognize the contribution of medications to falls (Bell et al, 2015;Turner et al, 2017). Whether clinicians consider residents' falls risk when initiating FRIDs has important implications because medications are a modifiable risk factor for falling, and avoidance of FRIDs may be an important strategy to minimize the risk of falls and fall-related injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al, 2017). There has been little previous research in the use of FRIDs in residents who are at risk of falls (Turner et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Further studies are needed to establish the efficacy of the FRID tools and to rationalize or simplify medication regimens for elderly patients who are prescribed medications associated with orthostatic hypotension and psychotropics [9]. Further research will be required to determine whether de-prescribing fall risk-inducing medications will effectively reduce the risk of falls in older people [9].…”
Section: Discussionmentioning
confidence: 99%
“…Turner at al. [9] conducted a cross-sectional study to review the fall risk resulting from psychotropics and medications that cause orthostatic hypotension. This study involved 383 Australian older people whose medications were analysed with the Fall-Risk-Increasing Drugs (FRIDs) tool [9].…”
Section: Outcome Measuredmentioning
confidence: 99%
See 1 more Smart Citation